2017
DOI: 10.3390/coatings7040051
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Concrete Surface Water Absorption upon Addition of Lactate Derived Agent

Abstract: Water tightness of a concrete cover layer is important, as it is typically used as a protective coating of the steel reinforcement. Water tightness can be impaired by crack formation or by permeability. A bacteria-based lactate-derived healing agent (HA) can be added to concrete to enhance the potential for restoration of water tightness. Bacterial conversion of the included carbon source results in CO 2 production and subsequent CaCO 3 precipitation, similar to the mechanism of concrete carbonation. Carbonati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 18 publications
(16 reference statements)
7
20
0
Order By: Relevance
“…Jonkers et al developed since 2006 in a series of studies a bacterial spore and an organic compound–based healing agent for providing autonomous healing potential to concrete under aerobic conditions (see and references therein, and). The specific healing agent contains organic compounds in the form of calcium salts of fatty acids such as calcium formate, calcium acetate, calcium glutamate, calcium propionate, and calcium lactate or lactate derivatives . In latter study, it was found that upon addition of a lactate‐derived bacteria‐based healing agent, surface water absorption of mortar specimen was decreased in the OPC‐based (CEM I) specimen but not (increased) in the blast‐furnace slag cement‐based (CEMIIIb) specimen …”
Section: Self‐healing Bioconcretementioning
confidence: 95%
“…Jonkers et al developed since 2006 in a series of studies a bacterial spore and an organic compound–based healing agent for providing autonomous healing potential to concrete under aerobic conditions (see and references therein, and). The specific healing agent contains organic compounds in the form of calcium salts of fatty acids such as calcium formate, calcium acetate, calcium glutamate, calcium propionate, and calcium lactate or lactate derivatives . In latter study, it was found that upon addition of a lactate‐derived bacteria‐based healing agent, surface water absorption of mortar specimen was decreased in the OPC‐based (CEM I) specimen but not (increased) in the blast‐furnace slag cement‐based (CEMIIIb) specimen …”
Section: Self‐healing Bioconcretementioning
confidence: 95%
“…Published lab-based studies have shown that, depending on the dosage of bacteria and lactate-based nutrients, cracks of up to 0.8 mm width can be sealed autonomously [14,16]. Healing of 0.8 mm wide cracks requires a dosage of 15 kg of B. alkalinitrilicuscomprising self-healing agent per m 3 of concrete mix , while a dosage of 5 kg/m 3 leads to the autonomous waterproofing of 0.4 mm wide cracks ( Figure 2) [17]. The composition of the healing agent used was 0.1% (w/w) dried B. alkalinitrilicus spores and 2% Yeast (w/w) extract both embedded in a lactate-based polymer matrix (97,7% w/w), latter functioning both as nutrient source and protective coating for the bacterial spores [21] and is commercially produced and marketed by Green-Basilisk B.V., The Netherlands.…”
Section: Autonomous Crack Repair By Limestoneforming Bacteriamentioning
confidence: 99%
“…A next generation selfhealing agent was therefore developed by the Delft group and in this one the active healing agent components (bacterial spores, yeast extract and lactate-derivatives) were pelleted using combined powder compression-and extrusion techniques which made the use of expanded clay carriers redundant [14]. Major advantage of the new generation healing agent is that it consists of 100% bio-based active ingredients not resulting in decrease of compressive strength of the resulting concrete if dosed correctly [21]. Activator of the healing agent is crack-ingress water what initiates germination of the bacterial spores.…”
Section: Development Of Bacteria-based Self-healing Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…This negative impact can be minimized by drying of lignocellulosic particles [17,18] or washing the particles or using additives such as calcium chloride and sodium silicate [19,20]. Alternatively, injection of carbon dioxide in the mixture can significantly improve the wood-cement compatibility [13], which also reduces the water absorption properties of the panels [21], and promote rapid strength development for the composites [22]. However, larger amount of cement is used in the CBCs for bonding in comparison to particles (cement:particles ratio is higher than 3:1), thus, the final products have higher density (> 1.3 g/cm 3 ) [2,4,23].…”
Section: Introductionmentioning
confidence: 99%